2020
DOI: 10.1038/s41564-020-0674-4
|View full text |Cite
|
Sign up to set email alerts
|

A MORC-driven transcriptional switch controls Toxoplasma developmental trajectories and sexual commitment

Abstract: Introductory T. gondii has a complex life cycle typified by an asexual development taking place in vertebrate, and a sexual reproduction which occurs exclusively in felids and thereby is less studied. The developmental transitions rely on changes in gene expression patterns, and recent studies have assigned roles for chromatin shapers, including histone modifications, in establishing specific epigenetic programs for each given stage. Here, we identified T. gondii … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
232
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(244 citation statements)
references
References 49 publications
(69 reference statements)
12
232
0
Order By: Relevance
“…We recently reported that the essential histone acetyltransferase (HAT) GCN5b operates in a multisubunit complex with at least two ApiAP2 factors, AP2IX-7 and AP2XII-4, to activate gene expression ( 38 ). In the current study, we found that AP2IX-4 and APXII-2 interact with the recently described MORC complex, which contains transcriptional repressive proteins, including histone deacetylase HDAC3 ( 24 ). Identifying AP2IX-4 as an interactor with MORC validates our previous observation that loss of AP2IX-4 results in upregulation of a subset of bradyzoite genes ( 23 ).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…We recently reported that the essential histone acetyltransferase (HAT) GCN5b operates in a multisubunit complex with at least two ApiAP2 factors, AP2IX-7 and AP2XII-4, to activate gene expression ( 38 ). In the current study, we found that AP2IX-4 and APXII-2 interact with the recently described MORC complex, which contains transcriptional repressive proteins, including histone deacetylase HDAC3 ( 24 ). Identifying AP2IX-4 as an interactor with MORC validates our previous observation that loss of AP2IX-4 results in upregulation of a subset of bradyzoite genes ( 23 ).…”
Section: Discussionsupporting
confidence: 52%
“…2 shows a volcano plot generated with P values (−log 10 P values) and fold change values (log 2 FC) for the 136 protein hits detected from mass spectrometry. Together, the proteins complexed with AP2IX-4 overlap the recently elucidated microrchidia (MORC) repressor complex that has been implicated in silencing genes associated with the T. gondii sexual stages ( 24 ). Thus, our findings bolster the observation that multiple AP2 factors recruit MORC to regulate gene expression and provide an explanation as to why the loss of AP2IX-4 resulted in the dysregulation of genes ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the Pf MORC sequence diverges from that of MORC proteins found in other eukaryotes, it is unclear what transcriptional role it might play with ISWI in P. falciparum . A recent study in another apicomplexan parasite, Toxoplasma gondii , showed that MORC associates with ApiAP2 transcription factors and a histone deacetylase (HDAC3) to transcriptionally silence specific cohorts of genes important for sexual differentiation (Farhat et al , ). This MORC/HDAC3 complex seems to modulate nucleosome positioning and/or histone acetylation to directly silence transcription or act as a barrier to neighboring euchromatin.…”
Section: Discussionmentioning
confidence: 99%